A Dynamical Model of the Heliosphere with the Adaptive Mesh Refinement. (May 2019) - Matsumoto, Tomoaki; Shiota, Daikou; Kataoka, Ryuho; Miyahara, Hiroko; Miyake, Shoko
Abstract: A three-dimensional time-dependent heliospheric model is developed with the adaptive mesh refinement (AMR) technique. The AMR code, SFUMATO, is adopted, which has been originally developed for star-formation problems. The solar wind model is based on the space weather forecast system, SUSANOO, and it is imposed on the inner boundary at r = 25 R ⊙ . The solar wind model is derived from magnetogram synoptic maps, which are observed daily. Using the potential field source surface models, the WS formula, and a few empirical laws, the MHD parameters at the inner boundary are reproduced. The heliospheric model here extends up to 14 au, and the AMR grid resolves the heliospheric current sheets and co-rotating interaction regions with refined resolutions. The AMR grid brings considerable improvement in the fine features in the outer region of r ≳ 2 au compared to the concentric nested grid, of which resolution has the relationship Δ x ∝ r, similar to spherical coordinates. The refinement criteria are based mainly on the distance from the Sun, the anti-parallel toroidal magnetic fields, and the density of the solar wind.